PENDEKATAN ANDRAGOGI KRISTEN BAGI ORANG DEWASA TUA DALAM GEREJA MASA KINI - Yusak Buing (Metanoia, 2022)
Education is the main thing needed by all humans in this world. In order to reach many and empower the body of Christ that has members with one another, education plays an important role in today's times, both for children and adults. In this case, education which is Christian education is education that specifically discusses Christian values, which plays an important role in today's church to equip adults or the body of Christ so that they can serve Christ in the church to the fullest